ASSESSMENT OF FACTORS INFLUENCING THE EFFICIENCY OF SECTORAL ACTIVITIES IN THE NATIONAL ECONOMY - Kozlovska, Solvita; Ūdre, Gunita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
To work effectively for commercial companies in different sectors of the economy, it is of interest to business owners, investors, management, employees, the state and society as a whole. The efficiency of commercial companies is crucial for the process of financial and economic decision-making. In Latvia, there have been neither in-depth research studies on the efficiency of financial activity, nor studies on the efficiency of certain sectors of the economy. The aim of the research is to summarize and analyse data on factors influencing the operational efficiency of commercial companies working in the national economy sectors: number of employees in the sectors, number of enterprises, value of exports and imports, personnel costs and number of employees in enterprises of a given sector, gross investments in material matters, land, machinery, equipment, non-financial investments in intangible assets and fixed assets, turnover, indicators of financial performance of enterprises, which provide aggregated information on liquidity, profitability and solvency of enterprises. The data processing used ibm spss statistics v21 method. The result of the research study is to group the factors that have a significant impact on the efficiency of the economic sector.